2010
DOI: 10.1002/acp.1706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training with added difficulties on RADAR detection

Abstract: Summary: Three experiments simulating military RADAR detection addressed a training difficulty hypothesis (training with difficulty promotes superior later testing performance) and a procedural reinstatement hypothesis (test performance improves when training conditions match test conditions). Training and testing were separated by 1 week. Participants detected targets (either alphanumeric characters or vehicle pictures) occurring among distractors. Two secondary tasks were used to increase difficulty (a concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Therefore, they all reported that current day procedures should be taught first and be given the most emphasis (about threequarters instead of half of the class) during training. This finding is consistent with the difficulty of training hypothesis Young et al [16] in that the more difficult tasks should be trained first because it leads to better transfer of skill and retention of learning.…”
Section: Perceived Effectiveness Of Training Ordersupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, they all reported that current day procedures should be taught first and be given the most emphasis (about threequarters instead of half of the class) during training. This finding is consistent with the difficulty of training hypothesis Young et al [16] in that the more difficult tasks should be trained first because it leads to better transfer of skill and retention of learning.…”
Section: Perceived Effectiveness Of Training Ordersupporting
confidence: 80%
“…There have been many demonstrations of parttask training compared to whole-task training in different domains [13,14,15]. Young et al [16] showed that the difficulty participants experienced in training can also influence their performance later. In their study, an unrelated secondary task was added to increase the task's difficulty during training.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if people are subjected to difficult problems in DCCS, then they would likely be able to reduce their correlation heuristic and violation of mass balance misconceptions in the CS task due to the difficulty hypothesis ( Schneider et al, 2002 ; Healy et al, 2005 ; Young et al, 2011 ). However, on account of cognitive load theory and people’s bounded working memory capacity ( Simon, 1959 ; Sweller, 1994 ; De Jong, 2010 ), it is also likely that if people are subjected to difficult problems in DCCS, then they would not be able to reduce their correlation heuristic and violation of mass balance misconceptions in the CS task.…”
Section: Background Sectionmentioning
confidence: 99%
“…For example, school children may be trained on simple and difficult problems in the classroom to prepare them for different problems in their exam. According to the difficulty hypothesis ( Schneider et al, 2002 ; Young et al, 2011 ), transfer performance in the CS task should improve when training is conducted using difficult climate problems in DCCS compared to simple problems. However, it is also possible that due to the predictions from cognitive load theory ( Sweller, 1994 ; De Jong, 2010 ), difficult training problems in DCCS may not lead to reductions in stock-flow misconceptions compared to simple training problems.…”
Section: Experiments 2: Effect Of Difficulty Of Problems In Reducing Smentioning
confidence: 99%
See 1 more Smart Citation